2005
DOI: 10.1177/0886109905274676
|View full text |Cite
|
Sign up to set email alerts
|

Computer Technology for the Feminist Classroom

Abstract: This article presents an evaluation of a social work course on oppression and diversity in which an interactive Web page was used to structure feminist learning experiences. Three assignments are described—an online diversity discussion board, a “digital poster” group research project, and the summary and critique of articles. The evaluation found that several processes that are key to a feminist classroom were achieved, including community building, collaboration, peer learning, empowerment, and the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
(27 reference statements)
0
12
0
3
Order By: Relevance
“…Some studies that report on student perceptions of online courses, indicate that students are positive about e-learning feeling that they learnt from the collaborative and reflective interaction with other students (Littlefield and Roberson 2005;Quinney 2005;RobertsDeGennaro et al 2005). The sharing of information through online discussion forums has been a source of support for students involved in practical social work placements (Quinney 2005;Roberts-DeGennaro et al 2005).…”
Section: Introductionmentioning
confidence: 94%
“…Some studies that report on student perceptions of online courses, indicate that students are positive about e-learning feeling that they learnt from the collaborative and reflective interaction with other students (Littlefield and Roberson 2005;Quinney 2005;RobertsDeGennaro et al 2005). The sharing of information through online discussion forums has been a source of support for students involved in practical social work placements (Quinney 2005;Roberts-DeGennaro et al 2005).…”
Section: Introductionmentioning
confidence: 94%
“…The findings indicate that fictional stories can help individuals understand some of the stressors that members of nonmajority groups have to deal with daily, and it can also help adult learners understand the impact of racism, sexism, and classism. Consistent with the Littlefield and Robertson (2005), the authors attempted to adhere to a feminist pedagogical framework and create a “liberatory” learning environment, which was interactive and collaborative.…”
Section: Discussionmentioning
confidence: 99%
“…Women may possibly express themselves without restrictions of patriarchy structures derived from classroom interactions, texts, and knowledge contents (Hughes, 1995;Tisdell, 1993). However, a web-based feminist learning experience such as online discussion, self-expression, digital poster group, and weblogs may play another learning opportunity, and further develop female learners' leadership (Littlefield & Roberson, 2005) and their transformation (Chu et al, 2012). Kelly, Pomerantz, & Currie (2006) also found that young female learners will develop effective learning and survival strategies in this environment.…”
Section: Introductionmentioning
confidence: 99%